Video education improves patients’ knowledge and satisfaction in treatment of solar lentigines with picosecond 755-nm alexandrite laser: A retrospective study - Liu, Jia-Wei; Tan, Yan; Chen, Tian; Qian, Yue-Tong; Zhang, Tao; Ma, Dong-Lai (Frontiers in Medicine, 2023)
Background Picosecond lasers are widely used in dermatologic and cosmetic practice. In clinical practice, informed consent for laser treatments is critical to ensure patients’ understanding of health information. Objectives To evaluate whether video-based informed consent improves patient comprehension and satisfaction. Methods The study was performed from August 1 to November 30, 2022. Solar lentigines patients who fulfilled the inclusion criteria were included. Before October 1, 2022, traditional informed consent methods were performed. In the subsequent 2 months, a video-based informed consent was used as an adjunct to traditional consenting methods. Finally, patient comprehension of relevant knowledge about laser treatment and client satisfaction were assessed. Results A total of 106 patients were included. The mean number of correct answers in the comprehension assessment in the video-based informed consent group was significantly higher than that in the traditional informed consent group (4.4 ± 1.2 vs. 3.4 ± 1.1, p < 0.001). Compared to the traditional informed consent group, more correct answers in the video-based informed consent group were provided by older patients (3.9 ± 1.2 vs. 2.9 ± 1.1, p = 0.004) and patients with lower education levels (4.1 ± 1.1 vs. 3.0 ± 1.2, p < 0.001). The mean satisfaction score in the video-based informed consent group was significantly higher than that in the traditional informed consent (27.8 ± 5.7 vs. 24.3 ± 6.2, p = 0.003). Conclusion Video-based informed consent helps patients learn clinical literacy more effectively and improves patient satisfaction, especially in those with lower education levels and older ages.